f ( x ) is a polynomial of degree 99. For exactly 100 (out of 101) integer values ranging from 0 to 1 0 0 , we have f ( x ) = x + 1 1 . Also, f ( 1 0 1 ) = 0 . For what value of a , 0 ≤ a ≤ 1 0 0 is f ( a ) = a + 1 1 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good approach which properly uses the condition that f ( x ) is a polynomial.
Nice solution, Roberto!
Same as mine.But I feel lazy to type!
I used an idea similar to Lagrange Interpolation to solve this problem, it's nice to see solutions that are much more simpler. Nice solutions!
5th row from the bottom, there is a factor of 101 missing from the numerator. Nice solution btw!
We know that
f
(
x
)
=
x
+
1
1
for all integers ranging from
0
to
1
0
0
except
a
. Thus,
(
x
+
1
)
f
(
x
)
−
1
=
0
for all integers ranging from
0
to
1
0
0
except
a
. This leads us to consider the 100 degree polynomial
g
(
x
)
=
(
x
+
1
)
f
(
x
)
−
1
, whose roots are the integers ranging from
0
to
1
0
0
except
a
. (There are no more roots because
g
is only of degree 100.) Therefore, we can write
g
(
x
)
=
c
⋅
x
−
a
x
(
x
−
1
)
(
x
−
2
)
⋯
(
x
−
1
0
0
)
,
for some nonzero constant
c
. But we are also given that
f
(
1
0
1
)
=
0
, which implies
g
(
1
0
1
)
=
−
1
. Plugging in
1
0
1
to the above equation yields
c
⋅
1
0
1
−
a
1
0
1
!
=
−
1
⟹
c
=
−
1
0
1
!
1
0
1
−
a
Thus we can now write
g
(
x
)
as
g
(
x
)
=
−
1
0
1
!
1
0
1
−
a
⋅
x
−
a
x
(
x
−
1
)
(
x
−
2
)
⋯
(
x
−
1
0
0
)
Now notice that from our definition of
g
(
x
)
we have
g
(
x
)
+
1
=
(
x
+
1
)
f
(
x
)
, which means that
−
1
is a root of
g
(
x
)
+
1
. Thus plugging in
x
=
−
1
into
g
(
x
)
+
1
should give us
0
:
−
1
0
1
!
1
0
1
−
a
⋅
−
1
−
a
(
−
1
)
(
−
2
)
(
−
3
)
⋯
(
−
1
0
1
)
+
1
=
0
,
and after some cancellation and rearranging we get
a
=
5
0
.
nice and clean approach
Consider g ( x ) : = ( x + 1 ) f ( x ) − 1 which is a polynomial with degree 1 0 0 . Note that the roots of g ( x ) are the 1 0 0 integers (From f ( x ) = x + 1 1 for these integers). And also note that g ( 1 0 1 ) = g ( − 1 ) = − 1 , as f ( 1 0 1 ) = 0 . Let the roots of g ( x ) be a 1 , a 2 , . . . , a 1 0 0 (which are the 1 0 0 integers.). Let a be the 'leftover' integer. Let g ( x ) = A ( x − a 1 ) ( x − a 2 ) . . . ( x − a 1 0 0 ) . Note that g ( 1 0 1 ) = ( 1 0 1 − a 1 ) ( 1 0 1 − a 2 ) . . . ( 1 0 1 − a 1 0 0 ) = 1 0 1 − a A ( 1 0 1 ! ) (Since a i ranges through 0 to 1 0 0 , except a , and thus 1 0 0 − a i ranges through 1 to 1 0 1 , except 1 0 1 − a ) and similarly g ( − 1 ) = A ( − 1 − a 1 ) ( − 1 − a 2 ) . . . ( − 1 − a 1 0 0 ) = ( − 1 ) 1 0 0 ( 1 + a 1 ) ( 1 + a 2 ) . . . ( 1 + a 1 0 0 ) = A ( 1 + a 1 ) ( 1 + a 2 ) . . . ( 1 + a 1 0 0 ) = a + 1 A ( 1 0 1 ! ) . Since g ( 1 0 1 ) = g ( − 1 ) = − 1 , 1 0 1 − a = a + 1 ⇒ a = 5 0 .
Exactly!!!!
Let g be a polynomial such that g ( x ) = ( x + 1 ) f ( x ) − 1 . The 1 0 0 values that satisfy f ( x ) = x + 1 1 are clearly the only zeros of g , since g is a polynomial of degree 1 0 0 . Observe that g ( − 1 ) = g ( 1 0 1 ) = − 1 . Now, let those 100 values that satisfy f ( x ) = x + 1 1 be x 1 , x 2 , … x 1 0 0 . g ( x ) can be written as A ( x − x 1 ) ( x − x 2 ) … ( x − x 1 0 0 ) , where A is a nonzero constant. Then g ( 1 0 1 ) = A ( 1 0 1 − x 1 ) ( 1 0 1 − x 2 ) … ( 1 0 1 − x 1 0 0 ) = 1 0 1 − a 1 0 1 ! A and also g ( 1 ) = A ( − 1 − x 1 ) ( − 1 − x 2 ) … ( − 1 − x 1 0 0 ) = A ( 1 + x 1 ) ( 1 + x 2 ) … ( 1 + x 1 0 0 ) = 1 + a 1 0 1 ! A . So we have g ( − 1 ) = g ( 1 0 1 ) ⇒ 1 0 1 − a 1 0 1 ! A = 1 + a 1 0 1 ! A ⇒ 1 0 1 − a = 1 + a since A is not zero. Solving this gives us a = 5 0 .
Let g ( x ) = ( x + 1 ) . f ( x ) − 1 . As f(x) is a polynomial of degree 99, g(x) is a polynomial of degree 100.
However, as f ( x ) = x + 1 1 for exactly 100 values of x from 0 ; 1 ; … ; 1 0 0 we have that g(x)=0 for all such values.
Let the values be x 1 ; x 2 ; … ; x 1 0 0 . Thus, g ( x ) = k . ( x − x 1 ) . ( x − x 2 ) … ( x − x 1 0 0 ) for some real constant k.
We have that g(-1)=-1 since g(-1)=(-1+1).f(-1)-1=-1 and g(101)=102.f(101)-1=-1 since f(101)=0.
Thus: k . ( − 1 − x 1 ) . ( − 1 − x 2 ) … ( − 1 − x 1 0 0 ) = k . ( 1 0 1 − x 1 ) . ( 1 0 1 − x 2 ) … ( 1 0 1 − x 1 0 0 ) .
However k cannot equal 0 because f(-1) is different from 0.
Thus, ( − 1 − x 1 ) . ( − 1 − x 2 ) … ( − 1 − x 1 0 0 ) =
( 1 0 1 − x 1 ) . ( 1 0 1 − x 2 ) … ( 1 0 1 − x 1 0 0 )
Let the value a for which f ( a ) = a + 1 1 be x 1 0 1
Then, ( − 1 − x 1 ) . ( − 1 − x 2 ) … ( − 1 − x 1 0 0 ) = ( 1 + x 1 ) . ( 1 + x 2 ) … ( 1 + x 1 0 0 )
= 1 + x 1 0 1 ( 1 + 0 ) . ( 1 + 1 ) … ( 1 + 1 0 0 )
and ( 1 0 1 − x 1 ) . ( 1 0 1 − x 2 ) … ( 1 0 1 − x 1 0 0 )
= 1 0 1 − x 1 0 1 ( 1 0 1 − 0 ) . ( 1 0 1 − 1 ) … ( 1 0 1 − 1 0 0 ) .
Since both the numerator are equal and non-zero, we must have that: 1 + x 1 0 1 = 1 0 1 − x 1 0 1 , thus x 1 0 1 = 5 0 .
Thus, the only value of a, 0 ≤ a ≤ 1 0 0 such that f ( a ) = a + 1 1 is 50.
Let g ( x ) = f ( x ) ( x + 1 ) − 1 . The problem implies that g ( x ) = 0 for 100 integer values from 0 to 100 except for a .
Also g ( − 1 ) = − 1 and g ( 1 0 1 ) = f ( 1 0 1 ) ⋅ 1 0 2 − 1 = − 1
Now, since g ( x ) is a polynomial of degree 100, then g ( x ) = A ( x − x 1 ) ⋯ ( x − x 1 0 0 ) = A x − a i = 0 ∏ 1 0 0 ( x − i )
g ( − 1 ) = 1 implies 1 = A − 1 − a i = 0 ∏ 1 0 0 ( − 1 − i ) = a + 1 A ⋅ 1 0 1 !
g ( 1 0 1 ) = 1 implies 1 = A 1 0 1 − a i = 0 ∏ 1 0 0 ( 1 0 1 − i ) = 1 0 1 − a A ⋅ 1 0 1 !
From both of these equations we obtain a + 1 = 1 0 1 − a ⇒ a = 5 0 as desired.
Consider f(x)=N/(x+1), where N is divisible by x+1. Since N=1 for x= all integers between 0 and 100 inclusive except one value (which we shall assume as a), N must be of the form: 1+k x(x-1)(x-2)...(x-100)/(x-a) Note that we define the value of f(x) at x=a or x= -1 to be their limiting values so that they are continuous (the reason for which shall become obvious as we proceed). We first determine k in terms of a so that N is divisible by (x+1) Put x=-1 and solve for N=0, for which we get, k=-(1+a)/{q(101)}, where q(n)=factorial of n (n belongs to N) Next we put f(101)=0: N=0; 1+k {q(101)}/(101-a) Putting above value of k, we get a=50 We can easily see that this is the odd one out among our set of natural numbers from 0 to 100 that would yield f(x)=1/(x+1) since (x-50) no longer exists in the numerator we constructed. Fortunately, neither does x=50 coincidentally yield 1/51; hence is the required answer.
Let q ( x ) = ( 1 + x ) f ( x ) − 1 Then except for one k in S = { 0 , 1 , 2 , . . . , 1 0 0 } , every integer in S is a root of q . Thus there exists α in R such that q(x)=\alpha \prod_{i=0}_{i\neq k}^{100} (x- i) Using the fact that q ( 1 0 1 ) = − 1 yields α = 1 0 1 ! 1 0 1 − k Finally, noticing that q ( − 1 ) = − 1 , and \prod_{i=0}_{i\neq k}^{100} (-1- i) = (-1)^{100}\frac{101!}{1+k} we get 1 0 1 ! 1 0 1 − k 1 + k 1 0 1 ! = − 1 ⟺ 1 0 1 − k = − 1 − k ⟺ k = 5 0
sorry that's α = − 1 0 1 ! 1 0 1 − k and so 1 0 1 ! k − 1 0 1 1 + k 1 0 1 ! = − 1 ⟺ k − 1 0 1 = − 1 − k and the final answer is, well, correct.
Consider the polynomial g ( x ) such that g ( x ) = ( x + 1 ) f ( x ) − 1 . Note that if f ( x ) = x + 1 1 , g ( x ) = 0 . Hence, each of the 1 0 0 values satisfying f ( x ) = x + 1 1 is a root of g ( x ) . We then can write g ( x ) as g ( x ) = x − a c ( x ) ( x − 1 ) ( . . . ) ( x − 1 0 0 ) , where a is the desired missing value.
Since f ( 1 0 1 ) = 0 , g ( 1 0 1 ) = 1 0 2 f ( 1 0 1 ) − 1 = 1 0 1 − a c ( 1 0 1 ) ( 1 0 1 − 1 ) ( . . . ) ( 1 0 1 − 1 0 0 ) so − 1 = 1 0 1 − a c ∗ 1 0 1 ! .
Also, g ( − 1 ) = ( − 1 + 1 ) f ( − 1 ) − 1 = − 1 − a c ( − 1 ) ( − 1 − 1 ) ( . . . ) ( − 1 − 1 0 0 ) so − 1 = − 1 − a − c ∗ 1 0 1 ! .
Equating our two equations, we find that a + 1 = 1 0 1 − a , so a = 5 0 .
f(x)= 1/x+1 for 100 integers between 0 to 100 we can write (x+1)f(x)-1 = p(x-a {1})(x-a {2})..............(x-a {100}) .....eqn 1 where a {1}, a {2}...... a {100} are integers belonging to [0,1,2,3.....100] Since the degree of f(x) is 99, therefore f(-1)=0 It is given that f(101)=0 On applying the above 2 conditions on equation 1, we get that a_{i} does not contain 50
Let P(x)=(x+1)f(x)-1, then P(x)=kx(x-1)...(x-100)/(x-a) P(101)=102f(101)-1=0.=> k.101!+101-a=0(I) f(x)=[kx(x-1)...(x-100)+(x-a)]/[(x-a)(x+1)] Q(x)=kx(x-1)...(x-100)+(x-a).Q(-1)=0.=>-101!k-a-1=0.(II) (I)+(II)=> a=50
Since 1 0 1 is a root of polynomial , we have f ( x ) = ( x − 1 0 1 ) ⋅ p ( x ) where degree of p ( x ) is 9 8 .
Now since f ( x ) = x + 1 1 for all values between 0 and 1 0 0 , we have p ( x ) = ( x + 1 ) ( x − 1 0 1 ) 1 Now its easy to see that , if x = a satisfies then x = 1 0 0 − a also satisfies the condition . now all the values except 5 0 work in pairs ( because 5 0 = 1 0 0 − 5 0 .
∴ we have a = 5 0
Let S be the set of all integers between 0 and 1 0 0 for which f ( x ) = x + 1 1 for all x ∈ S . From the problem statement, we have ∣ S ∣ = 1 0 0 .
Since 1 0 1 is a root of f ( x ) , we can rewrite f as f ( x ) = ( 1 0 1 − x ) Q ( x ) , where Q ( x ) is a polynomial of degree 9 8 . Hence, Q ( x ) = 1 0 1 − x f ( x ) = ( x + 1 ) ( 1 0 1 − x ) 1 for all x ∈ S . Define P ( x ) = ( x + 1 ) ( 1 0 1 − x ) 1 . Then, substituting 1 0 0 − x into the equation, we get P ( x ) = P ( 1 0 1 − x ) . So x ∈ S if and only if 1 0 0 − x ∈ S (*).
Let a be an integer from 0 to 1 0 0 which does not belong to S . From (*), we conclude that both a and 1 0 0 − a do not belong to S . But, there can be at most one such a . So, we must have a = 1 0 0 − a ⇔ a = 5 0 .
Let f ′ ( x ) be defined in the same way as f above, except
that f ′ ( a ) = a + 1 1 .
Since f ′ ( 1 0 1 ) = 0 , this means ( x − 1 0 1 ) is a factor of
f ′ ( x ) . Let h ′ ( x ) = x − 1 0 1 f ′ ( x ) = ( x + 1 ) ( x − 1 0 1 ) 1 with 0 ≤ x ≤ 1 0 0 Similarly let h ( x ) be x − 1 0 1 f ( x ) .
h ′ ( x ) is even; specifically, h ′ ( x ) = h ′ ( 1 0 0 − x ) .
This means that if h ′ ( a ) = h ( a ) then h ′ ( 1 0 0 − a ) = h ( 1 0 0 − a ) .
But it was specified that only one value of f differs from
f ′ (on the domain we are looking at), therefore only one
value of h ( x ) can differ from h ′ ( x ) . So we we must have
a = 1 0 0 − a , i.e. a = 5 0 .
This solution commits several mistakes:
The assumption of "let f ′ ( x ) be defined in the same way as f above" is invalid. There is no such polynomial function of degree 99 that satisfies all of those conditions (which is the point of this question).
There is no strong correlation between 2 polynomial functions that satisfy f ( x i ) = g ( x i ) for n values, unless you know much more about their degrees. For example, there are infinitely many cubic polynomials which satisfy f ( 0 ) = f ( 1 ) = 0 .
Saying that h ′ ( x ) = ( x + 1 ) ( x − 1 0 1 ) 1 makes it a rational function, and not a polynomial. Just because you (implicitly) claim that it is a polynomial, doesn't make it so.
I tried for a long time to try and write this rigorously without having to introduce f ′ and h ′ .. once you realize that f ( x ) = f ( 1 0 0 − x except at a , the idea is obvious but it was tough to put down in rigorous fashion.
Replying to CM notes: I should also have mentioned that f'(x) and h'(x) don't have to be polynomials. But your point (2) seems to be valid, so my formal approach doesn't work. I guess I should have stuck with what I originally had in mind :)
Problem Loading...
Note Loading...
Set Loading...
It is given that for 100 values from 0 to 100 the equation f ( x ) ( x + 1 ) = 1 .
But it is a well known theorem that if a polynomial g(x), with d e g ( g ) = n , that satisfies g(x)=0 for n values a 1 , a 2 , . . . , a n , then g ( x ) = r ( x − a 1 ) ( x − a 2 ) . . . ( x − a n ) , for some real constant r .
Since f ( x ) ( x + 1 ) − 1 = g ( x ) = 0 is satisfied for 100 values and d e g ( g ) = 1 0 0 , then
f ( x ) ( x + 1 ) − 1 = x − a r x ( x − 1 ) ( x − 2 ) . . . ( x − 1 0 0 ) , for the specified value a.
Now substituting x = − 1 we get that − 1 = r × − 1 − a − 1 0 1 ! since there are and odd amount of negative terms in the numerator, and so r = 1 0 1 ! − ( a + 1 ) .
Now we can use the given information that f ( 1 0 1 ) = 0 , which implies that substituting x = 1 0 1 will give
− 1 = r × 1 0 1 − a ( 1 0 1 − 1 ) ( 1 0 1 − 2 ) . . . ( 1 0 1 − 1 0 0 )
− 1 = 1 0 1 ! − ( a + 1 ) × 1 0 1 − a 1 0 1 !
− 1 = 1 0 1 − a − ( a + 1 )
a − 1 0 1 = − a − 1
2 a = 1 0 0 or a = 5 0 .